PHYSICOCHEMICAL CHARACTERISTICS ON PRODUCTS NATURAL FERMENTATION OF COW AND GOAT MILK - A. D., Seftyan; Okarini, I. A.; Mariani, N. P. (Jurnal Peternakan Tropika, 2019)
The research aim to know physicochemical characteristics (color, consistency, pH and dry matter) of natural fermented cow's milk and goat's milk. The study was conducted for 2 months (April - June 2018) at the Food Analysis Laboratory of the Faculty of Agricultural Technology, Udayana University, Denpasar. Fresh cow's milk is obtained from CV. Margo Utomo on Jl. Batam Island, No. 10, Denpasar. Fresh goat milk is obtained from UD. Bali Sari Wangi in Sepang Village, Busungbiu District, Buleleng Regency. The design used in this study was Factorial Randomized Group Design (RAKF) with 2 factors and 3 replications. The first factor is the type of milk, namely S1 (100% cow's milk), S2 (50% cow's milk + 50% goat's milk) and S3 (100% goat's milk). The second factor is the duration of fermentation, namely W0 (0 hour control), W10 (10 hours fermentation) and W20 (20 hours fermentation). The variables observed were color, consistency, pH and dry matter. The results of this study found that there were significant interactions (P<0.05) between the type of milk and the duration of fermentation on the variable pH. The type of milk had a significant effect (P<0.05) on pH, consistency and dry matter, but there were no significant differences (P>0.05) on color values. The fermentation time factor showed significantly different (P<0.05) on objective results (pH and dry matter) and subjective favorite values ??(color and consistency). It can be concluded that the fermentation time can increase the consistency and dry matter, and reduce the color and pH values. The type of milk does not affect the color of sour milk products, but can increase the consistency and dry matter. Keywords: physicochemical, milk type, time of fermentation.